Mengukur Kinerja Rantai Pasok Pada Agroindustri Tahu Dan Tempe: Aplikasi Model Supply Chain Operations Reference (SCOR) - Novi Rosanti; Dian Rahmalia; I Rani Mellya Sari; Varingan Prianando Tambunan; Rani Juniarti (Politeknik Negeri Lampung., 2025)
The study focuses on analyzing the supply chain of tofu and tempeh agro-industry in Lampung Province using a survey method. The research was conducted in Lampung Province, specifically in Bandar Lampung, Central Lampung, and Tulang Bawang. The study involved 154 respondents, including 142 tofu and tempeh producers and 12 soybean suppliers. The analysis utilized the Food Supply Chain Network (FSCN) and Supply Chain Operations Reference (SCOR) methods to examine the tofu and tempeh agro-industry supply chain. It was discovered that the flow pattern of the supply chain ran smoothly, encompassing product, information, and financial flows without encountering any impediments. The retailers/PRIMKOPTI and the tofu and tempeh agro-industry exhibited exceptional supply chain performance, particularly in reliability, responsiveness, and agility. The retailers/PRIMKOPTI supply chain was noted for its flexibility and lower total supply chain costs, indicating efficient cost management. Meanwhile, the tofu and tempeh agro-industry displayed excellent order fulfillment and very short cash-to-cash cycle time, demonstrating high responsiveness and efficient inventory management.